SENI DAN WAWASAN DUNIA: REPRESENTASI YESUS DALAM FILM SEBELUM DAN SESUDAH 1968 - Eric Gunawan (Universitas Kristen Satya Wacana, 2017)
In 1968, western democracy experienced a challenge and an impact to the birth of a new generation of post-war world called Flower Generation. The influence of this movement is not only on politics but also on lifestyles. Jesus' representation in film production before and after 1968 also changed significantly. Cinematographic technology is not the only cause of the change, the insights of the world play a role and burden the representation of Jesus. This paper wants to analyze how the insights of the world infiltrate the film and contribute to Jesus' representation. The analysis will use Eisenstein's pathos theory to understand the process of film pathos construction. Implementation of this theory will be used to read the representation of Jesus in two films by pioneer directors of the flow of Italian Neoealism, Pasolini and Rossellini. Scene to be analyzed from both films is the scene of Suffering in the Garden of Gethsemane.